Menentukan Tingkat Kesejahteraan Provinsi Kalimantan Tengah Dengan Penerapan Algoritma K-Means Clustering Menggunakan Rapidminer - R Rahmahwati (LPPM STIKOM Tunas Bangsa, 2023)
One of the key problems of local governments is poverty, and Central Kalimantan in Indonesia is one of those local governments. Due to the incorrect definition of impoverished households at the time of data collection, the municipal administration has created a number of initiatives and services that assist community welfare, but they have not been deemed functional. This study's objective is to use a clustering method to identify the level of regional poverty. The clustering method, which makes use of RapidMiner's standard data mining stages, was applied in this investigation. This work develops a method that can identify poor areas and categorize them into three groups—low, medium, and high—using a more precise computation approach